Man of iron Thomas Telford and the building of Britain - Glover, Julian (Bloomsbury Publishing, 2017)
The enthralling biography of the shepherd boy who changed the world with his revolutionary engineering and whose genius we still benefit from today. Thomas Telford may have been born into poverty but he became one of Britain's most important engineers, changing the shape of Britain forever; the creations that resulted from his skill, ambition and obsessive hard work span its length and breadth still. For too long, his extraordinary achievements have been overlooked, and his life left unexamined. Julian Glover now brings forward the man behind the name. There is brilliance and beauty in Thomas Telford's work. With his revolutionary vision, Telford invented the modern road and created the backbone of our national road network, tying England, Scotland, Ireland and Wales together, resulting in his being dubbed 'The Colussus of Roads'. His elegant bridges are the greatest of the pre-twentieth century, the Menai Bridge a wonder of its time and our own while the famous Pontcysyllte aqueduct in Wales with its dramatic and alarming exposed heights is a UNESCO world heritage site and still a huge draw for tourists. Yet Telford was no lone genius and his engineering triumphs were a physical manifestation of a new industrial and imperial power: Great Britain. It was an age of incredible ingenuity and ambition and rivalries ran high. It was a time of great energy and drama - and possibilities. Drawing on colourful contemporary accounts and travelling by horse to understand better the journeys we undertook before Telford's work transformed them, Julian Glover examines the stories behind Telford's greatest achievements and explores what in that time enabled him to flourish. At once intimate and expansive, this illuminating biography brings to life that most creative of eras and places Telford both at its heart and amongst the ranks of our greatest Britons
Keywords: Telford, Thomas -- 1757-1834; Geschichte 1700-1800; Geschichte; Großbritannien; Telford, Thomas / 1757-1834; Civil engineers / Great Britain / Biography; Civil engineering / Great Britain / History / 18th century; Civil engineering; Civil engineers; Great Britain; 1700-1799; Biography; History; Biografie